Evaluación del tiempo termal óptimo en los pastos para bovinos pastoreados en la parroquia Alaquez, cantón Latacunga. - Manobanda Quillupangui, Dayana Elizabeth (2021)
The present investigation was carried out in the province of Cotopaxi, in the Canton Latacunga, Sector Verde Cocha with the objective of with the objective of evaluating the optimal thermal time in a fodder with the purpose of determining the amount of accumulated temperature in relation to the NDF of the grasses for regrowth to have a constant quality, determine the cost benefit and evaluate the body condition of the animals thus determining the viability of the research for which bromatological and laboratory examinations were carried out.The field study was carried out at Farm , and it began by placing 6 thermometers of high and low temperatures in a determined paddock, which recorded the information of the temperatures 6 am and 6 pm during the time that the investigation lasted, started. On day 0 (15-ene-2021), the first sample was taken and sent to the laboratory for bromatological analysis, obtaining an FDN of 49.6, the following sample of the fooder mixture was sent 30 days after the re-growth (día 14-feb-2021) for another bromatological analysis obtaining a FDN of 44.00 with a thermal sum of 389.5 °C and it was culminated with the collection and then the third sample was sent to the next 10 days (24-feb-2021) for analysis with a FDN of 47.6 with a thermal sum of 434.5°C.For this research work 9 cows were used.3 in the first third of lactation, 3 in the second third of lactation, and 3 in the third of lactation,. Weights were taken from them, a record of daily milk production was kept, and blood samples were taken and sent to the BUN and in urine for ketone body analysis With the new grazing management, production increased from 13.3 lts / day to 16 lts / day in average cow / day.